2023
DOI: 10.1140/epjc/s10052-023-11199-2
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the sources of ionizing radiation in superconducting qubits

Abstract: Radioactivity was recently discovered as a source of decoherence and correlated errors for the real-world implementation of superconducting quantum processors. In this work, we measure levels of radioactivity present in a typical laboratory environment (from muons, neutrons, and $$\gamma $$ γ -rays emitted by naturally occurring radioactive isotopes) and in the most commonly used materials for the assembly and operation of state-of-the-art superconducting qubits. We present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…of radioactivity in the laboratory environment and further simulation studies of the Fermilab-SQMS/INFN-LNGS Round Robin chip show that about 64% of particle interactions would be due to 𝛾 radiation in an above-the-ground facility, whereas about 36% would be due to muons from cosmic rays, followed by a trace amount of contribution from neutron radiation. In comparison, rates at the 1.4 km-deep LNGS facility are calculated to be almost exclusively due to 𝛾 radiation as the thick rock layer acts as a barrier to muons [10]. Particle interaction rates similar to the ground-level estimates of this study were also reported in ref.…”
Section: Jinst 18 P12005supporting
confidence: 83%
See 4 more Smart Citations
“…of radioactivity in the laboratory environment and further simulation studies of the Fermilab-SQMS/INFN-LNGS Round Robin chip show that about 64% of particle interactions would be due to 𝛾 radiation in an above-the-ground facility, whereas about 36% would be due to muons from cosmic rays, followed by a trace amount of contribution from neutron radiation. In comparison, rates at the 1.4 km-deep LNGS facility are calculated to be almost exclusively due to 𝛾 radiation as the thick rock layer acts as a barrier to muons [10]. Particle interaction rates similar to the ground-level estimates of this study were also reported in ref.…”
Section: Jinst 18 P12005supporting
confidence: 83%
“…Strategies considered so far to mitigate the effect of high-energy particles include improving the design of chips with phonon and quasiparticle traps or membrane structures [11][12][13][14][15][16], adding shielding from natural radiation [10], distributing QEC across separate chips [17], and using co-located transition-edge sensors (TES) to detect energy transmission into the qubits from ionizing radiation [18]:…”
Section: Jinst 18 P12005mentioning
confidence: 99%
See 3 more Smart Citations